Management of ischemic risk events in patients with multifocal atherosclerosis and type 2 diabetes mellitus - O. L. Barbarash; V. V. Kashtalap (Атеротромбоз, 2020)
The review article presents current positions about prevalence of multifocal atherosclerosis and type 2 diabetes mellitus in patients with coronary artery disease (CAD). Existing approaches to the assessment and management of high risk of ischemic events in such patients are identified. Based on the results of clinical trials, the main positions have been identified on risk prevention of cardiovascular complications in patients with combination of multifocal atherosclerosis and type 2 diabetes mellitus. The results of the COMPASS study on the use of a combination of rivaroxaban 2.5 mg twice a day and a low dose of acetylsalicylic acid in patients with CAD and/or multifocal atherosclerosis are presented, which is accompanied by a significant reduction in the risk of cardiovascular events. This approach demonstrated a increase in the risk of massive bleedings, but mainly in the first year of treatment and without significant subsequent increase. At the same time, in the group of combination therapy rivaroxaban and acetylsalicylic acid there was no increase in the frequency of the most severe bleeding - fatal, intracranial and into the critical organs, compared to the group of monotherapy of acetylsalicylic acid. These two facts show a perfectly acceptable level of hemorrhagic risk for translation into real clinical practice. Hemorrhagic risk management capabilities were considered in a CoMPASS study by prescribing proton pump inhibitors to patients. The data on the COMPASS sub-analysis on evaluation of effectiveness and safety of combined antithrombotic therapy in patients with CAD and/or multifocal atherosclerosis and type 2 diabetes mellitus are presented. They showed the possibility of usage such approach in patient management in routine clinical practice. Patients with very high risk of ischemic events: ischemic heart disease and multifocal atherosclerosis, as well as type 2 diabetes mellitus, particularly need to improve approaches to antithrombotic therapy.